Evidence-Based Practice for the Use of Internal Strategies as a Memory Compensation Technique After Brain Injury: A Systematic Review. Issue 4 (July 2016) - O'Neil-Pirozzi, Therese M.; Kennedy, Mary R.T.; Sohlberg, McKay M.
Abstract : Objective: To complete a systematic review of internal memory strategy use with people who have brain injury and provide practitioners with information that will impact their clinical work. Methods: A systematic literature search to identify published intervention studies that evaluated an internal memory strategy or technique to improve memory function of individuals with brain injury. Relevant data from reviewed articles were coded using 4 clinical questions targeting participants, interventions, research methods, and outcomes. Results: A comprehensive search identified 130 study citations and abstracts. Forty-six met inclusion/exclusion criteria and were systematically reviewed. Visual imagery was most frequently studied, in isolation or in combination with other internal strategies. Despite significant variability in research methods and outcomes across studies, the evidence provides impetus for use of internal memory strategies with individuals following brain injury. Conclusions: Individuals with traumatic brain injury may benefit from internal memory strategy use, and clinicians should consider internal memory strategy instruction as part of intervention plans. Further research needs to better delineate influences on intervention candidacy and outcomes. Abstract : Supplemental Digital Content is Available in the Text.